Roommate effects in health outcomes. (16th July 2019) - Frijters, Paul; Islam, Asad; Lalji, Chitwan; Pakrashi, Debayan
Abstract: We use randomized roommate assignment in dormitories in a college in Kolkata in India to examine peer effects in weight gains among roommates. We use administrative data on weight, height, and test scores of students at the time of college admission and then survey these students at the end of their first and second years in college. We do not find any significant roommate specific peer effect in weight gain. Our results rather suggest that an obese roommate reduces the probability that the other roommates become obese in subsequent years. We examine potential mechanism using survey data on students' eating habits, smoking, exercise, and sleeping patterns. We find that obese roommates sleep longer, which in turn improves the sleep pattern of others, which might explain the weak negative effect of obese roommates on the weight of others in the same room.